PENINGKATAN KETERAMPILAN MENULIS TEKS BIOGRAFI MELALUI TOKOH IDOLA OLEH SISWA KELAS X SMA NEGERI 1 LAWE BULAN TAHUN PEMBELAJARAN 2021/2022 - Nopita Panjaitan; Ati Rosmiati (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
This study aims to determine the Improvement of Writing Skills..Biographical Texts..Through Idol Figures By Students..Class..X SMA Negeri 1 Lawe Month in the Academic Year 2021/2022. The population in this study were all students of class X SMA Negeri 1 Lawe Bulan in the 2021/2022 academic year, totaling 92 students, consisting of 4 classes. The sample in this study was 21 students, namely class X IPA 1 which was taken using a purposive sampling technique or determined sampling. Based on the results of the research and discussion that have been described in the previous chapter, it can be concluded that the Improvement of Biographical Text Writing Skills Through Idol Characters by Class X Students of SMA Negeri 1 Lawe Month in the 2021/2022 Academic Year. This is evident from the average value of the initial test of students' Biographical Text Writing Ability is 59.05 with a standard deviation of 8.41 and an increase in the final test result score with an average value of 80.24 with a standard deviation of 5.66. the student and if it is associated with the Indonesian KKM score for high school is 75, then the ability to write biographical texts for the final test of students is included in good ability. In addition, the observation value > ttable which is 9.35 > 2.08, thus from the results of testing the hypothesis above, it can be concluded that there is an increase in Biographical Text Writing Skills through Idol Figures by Class X Students of SMA Negeri 1 Lawe Month in the 2021/2022 Academic Year